WinMLR program for the determination of sorbic and benzoic acids in food samples. (1st November 2021) - Danchana, Kaewta; Jitthiang, Prapatsorn; Uraisin, Kanchana; Cerdà, Víctor
Abstract: The program WinMLR has been developed to quantify sorbic and benzoic acids in soft drinks, fruit juices, and soy sauce by making a multilinear regression treatment of experimental data to a linear combination of standard signals. The spectra of sorbic and benzoic acid and samples were obtained from a conventional spectrophotometer, which has been saved in an ASCII file to be applied with the WinMLR program. Before to determine sorbic and benzoic acids in samples, the wavelength validation and calibration parameters were studied. Standard solutions of sorbic and benzoic acids were used for the calibration parameters to measure the individual analyte. If the sample has simultaneously both compounds, it is better to choose the synthetic mixture for the calibration parameters. This technique provides a good recovery in the range of 80.4–104.8% without a complicated and expensive instrument.